A spear flap surgical revision - Ernesto De Piano; Pietro Rubegni; Vittoria Cioppa (PAGEPress Publications, 2024)
A 55-year-old male presented with a recurrent infiltrative basal cell carcinoma of the right nasal ala. Previous incomplete excision was repaired with second intention healing resulting in a contracted ala with columellar deviation and nostril asymmetry. [...]